IMPLEMENTASI KURIKULUM MERDEKA UNTUK MENGEMBANGKAN KREATIVITAS PESERTA DIDIK DI SEKOLAH DASAR - Hasmiati, Hasmiati; Fawzani, Nurul; Muhlis, Wachida (Jurnal Pendidikan Dasar, 2023)
In an effort to improve the quality of education, various ways are taken, such as curriculum changes that adjust to the needs of students, the demands of society, and the times. One of them is the development of an independent learning curriculum. The world of education today does not only require cognitive abilities but also requires creativity that makes students more productive. Therefore, this research aims to examine the implementation of the independent curriculum towards the development of students' creativity. This research uses a type of library research through a qualitative approach. The data collection technique in this study uses documentation techniques in the form of notes, transcripts, books, newspapers, magazines, inscriptions, minutes, research results, and so on. The collected data were then analyzed using descriptive methods. The results showed that the form of implementing an independent curriculum in elementary schools is the utilization of technology, preparation of learning tools, implementation of learning strategies that are in accordance with interests and talents, and learning is adapted to the situation and conditions of the environment, as well as local wisdom, socio-economics and providing space for students to learn collaboratively. So it can be understood that the implementation of an independent curriculum has an impact on increasing the creativity of students to produce innovations in education